Seleção de rizobactérias visando o controle biológico da murcha-de-esclerócio em tomateiro (Solanum lycopersicum L.) - Barbosa, Rosianne Nara Thomé (2009)
The southern blight caused by Sclerotium rolfsii is one of the most important diseases of tomato in tropical countries. The control is difficult and it is possible to use antagonist microorganisms, once conventional controls are not efficient. The use of rhizobacteria is one of viable disease control and on reduction or replace for the chemical products on plant disease control, meanly that caused by soil pathogen. The aim of this work was select rhizobacteria capable to control the southern blight with no effect on tomato growth and investigate the correlation of antibiosis mechanism and inhibition of oxalic acid diffusion with the control of disease. Methodological adjustments for induction of southern blight with no plant wounds were preview performed using 2, 4, 8 e 16 g of colonized rice.L-1 mixed on soil and 2, 4, 6 e 8 sclerotia or micelial discs deposited on soil surface. The selection of rhizobacteria was performed on greenhouse through six cycles of massal selection and the best isolates were revaluated in three experiments using the disease severity and plant growth as variables. All the isolates were evaluated for antibiosis tests and inhibition of oxalic acid diffusion in vitro. The results demonstrated that the mixed of 8 g of colonized rice.L-1 on the soil is the best concentration and inoculum source for the pathogen inoculation with no wounds; the 38291 isolate was the only to restrict the pathogen development in vitro through antibiosis and to control the southern blight in vivo. The 31233, 32238, 33282 e 41296 isolates promoted control of southern blight on greenhouse conditions with no activity detected in in vitro assays.